A&T Bangladesh Maternal Nutrition Endline Survey 2016: Households - Recently Delivered Women - International Food Policy Research Institute (International Food Policy Research Institute, 2020)
This dataset is the result of the household/recently delivered women (RDW) survey conducted to gather data for the Maternal Nutrition Endline as a part of an impact evaluation study of Alive & Thrive (A&T) interventions delivered through Building Resources Across Communities' (BRAC) Essential Health Care (EHC) Program in Bangladesh. A&T is a global initiative that supports the scaling up of nutrition interventions to save lives, prevent illnesses, and contribute to healthy growth and development through improved maternal nutrition, breastfeeding and complementary feeding practices. In setting its country program goal for Bangladesh in this phase of its study, A&T decided to focus on demonstrating the feasibility of integrating a package of maternal nutrition interventions in a large-scale Maternal, Newborn, and Child Health (MNCH) program. Maternal nutrition should receive equal priority as child nutrition and the A&T program of BRAC already have developed an effective strategy through improving IYCF practices. The objective of this impact evaluation is to assess the impact of integrating nutrition-focused behavior change communication (BCC- interpersonal counselling and mass communication) and community mobilization into BRAC's rural MNCH program on: 1) coverage and utilization of key maternal nutrition interventions; 2) consumption of diversified and adequate amount of foods and micronutrients by pregnant and postpartum women; and 3) early breastfeeding practices. In addition, factors affecting integration of nutrition interventions into a well-established community-based MNCH program platform through frontline health workers and social mobilization were examined. The study used a cluster-randomized design with repeated cross-sectional surveys at baseline and endline. As with the baseline, the endline survey used the same ten subdistricts from four districts (Mymensingh, Rangpur, Kurigram, and Lalmonirhat) in which BRAC's existing rural MNCH project is in place have been selected randomly to provide intensified maternal nutrition interventions. Another 10 subdisctricts/upazilas from the same four districts have been selected as comparison for the evaluation. It was conducted between July–August 2016 by the team from International Food Policy Research Institute (IFPRI), in collaboration with the survey firm, Data Analysis and Technical Assistance, Ltd. (DATA). The endline survey had three components: 1) Household survey for recently delivered women (RDW) and their husbands, 2) Household survey for pregnant women (PW) (with detailed dietary recall), and 3) a Frontline health workers survey (Shasthya Shebika (SS) and Shasthya Kormi (SK)). The household survey for recently delivered women (RDW) and their husbands captured the main impact indicators for A&T (consumption of iron and folic acid (IFA) and calcium, maternal dietary diversity, quantity and quality of diet, breastfeeding practices, and functional outcomes), use of antenatal care services (ANC) and exposure to A&T’s intervention platforms, and a variety of other data related to the use of the interventions. This included data on caregiver knowledge and perceptions about maternal nutrition, caregiver resources (such as education, physical and mental health, decisionmaking power and domestic violence) and household resources (such as household composition, socioeconomic status, and food security). The husband questionnaire provided data on husband’s knowledge of maternal nutrition during wife’s pregnancy, and husband’s practices to support his wife to have optimal nutrition during pregnancy.